A Phase II Study of Neoadjuvant Stereotactic Radiosurgery for Large Brain Metastases: Clinical Trial Protocol. Issue 2 (1st November 2019) - Takami, Hirokazu; Nassiri, Farshad; Moraes, Fabio Y; Zadeh, Gelareh; Bernstein, Mark; Conrad, Tatiana; Berlin, Alejandro; Laperriere, Normand; Millar, Barbara-Ann; Shultz, David Benjamin; Kongkham, Paul
Abstract: BACKGROUND: Brain metastases which require resection are treated with surgery followed by whole brain radiation therapy or postoperative cavity boost stereotactic radiosurgery (POCBS). Recently a novel strategy using neoadjuvant stereotactic radiosurgery (NaSRS) followed by resection was reported, demonstrating lower rates of postoperative leptomeningeal dissemination (LMD) and symptomatic radiation toxicity compared to a comparative cohort of patients treated with postoperative SRS. OBJECTIVE: To determine if the rate of symptomatic radiation toxicity at 1 yr in patients who receive NaSRS differs significantly from historical rates for patients treated with POCBS. METHODS: This is a multi-center, non-randomized, open phase II clinical trial. A total of 30 patients with up to 10 brain metastases, at least 1 of which is appropriate for surgical resection, will be enrolled for over 4 yr. All enrolled patients will be assigned to receive NaSRS followed by surgery. EXPECTED OUTCOME: This study will clarify whether symptomatic radiation toxicity caused by NaSRS is significantly decreased compared to historical rates associated with POCBS. Secondary endpoints will include 1-yr local control (LC) of the treated lesion, 1-yr rates of LMD, median survival and 2-yr rates of progression-free and overall survival. Tertiary analyses will include correlation between LC and radiation toxicity with pretreatment clinical factors, serum markers, radiomic features, and molecular assessments of the resected tumors. DISCUSSION: This prospective study will determine the toxicity associated with NaSRS and provide additional quantitative metrics of efficacy for future comparative trials.